Strategic management of the enterprise using the system of strategic management accounting in conditions of sustainable development - Shmatkovska, Tetiana; Volynets, Lyudmyla; Dielini, Maryna; Magopets, Olena; Kopchykova, Inna; Kytaichuk, Tetiana; Popova, Yuliia (My University, 2022)
The article examines and substantiates the principles of applying the system of strategic accounting management in the process of planning and management of enterprises. The role of accounting and analytical support in ensuring sustainable development is outlined. The need to strengthen the role of the enterprise`s analytical apparatus in making strategic management decisions in the process of long-term planning of business entities is justified. The application of the organizational model of building a strategic analytical system of the enterprise in the aspect of ensuring the successful implementation of the principles is proposed in strategic accounting management in order to improve the efficiency of the enterprise`s functioning.
Keywords: Accounting; Analytical support; Analytical support of management decisions; Accounting system of the enterprise; Strategic accounting management; Strategic analytical system of the enterprise; Strategic management